Strength enhancement of geotextile-reinforced carbonate sand. Issue 2 (April 2019) - Goodarzi, Saeed; Shahnazari, Habib
Abstract: The mechanical behavior of carbonate sand reinforced with horizontal layers of geotextile is invetigated using a series of drained compression triaxial tests on unreinforced and reinforced samples. The main factors affecting the mechanical behavior such as the number of geotextile layers, their arrangement in specimens, confining pressure, particle size distribution, geotextile type and relative density of samples were examined and discussed in this research. To make a precise comparison between the behavior of reinforced siliceous and carbonate sand, triaxial tests were performed on both types of sands. Results indicate that geotextile inclusion increases the peak strength and strain at failure, and significantly reduces the post-peak strength loss of carbonate specimens. The amount of strength enhancement rises as the number of geotextile layers increases while two other parameters including confining pressure and particle size affect adversely. The strength enhancement of reinforced carbonate sand is greater than the corresponding siliceous sample at high axial strains. Reinforced and unreinforced carbonate specimens exhibit more contractive behavior than their corresponding siliceous samples and tend to dilate at higher axial strains. By increasing the relative density of the samples, the peak strength of reinforced specimens rises due to enhanced interlocking between geotextile layers and sand particles. This process continues as long as the geotextile is not ruptured. The utilization of geotextiles with high mass per unit areas was found to be uneconomical due to slight differences between the strength augmentation of geotextiles with high and low mass per unit areas. It should be noted that geotextile layers limit the lateral expansion of specimens which leads to changing the failure pattern from a shear plane to bulging between the adjacent layers of geotextile.